Prime valued polynomials and class numbers of quadratic fields - Richard A. Mollin (International Journal of Mathematics and Mathematical Sciences)
It is the purpose of this paper to give a survey of the relationship between the class number one problem for real quadratic fields and prime-producing quadratic polynomials; culminating in an overview of the recent solution to the class number one problem for real quadratic fields of Richaud-Degert type. We conclude with new conjectures, questions and directions.